Effect of Dietary Coriander Seed Powder Supplementation on the Serological and Immunological Parameters of Broilers - Chandel, Rahul Singh; Sihag, Zile Singh; Sihag, Sajjan; kumar, sushil (Indian Journal of Animal Nutrition, 2021)
An investigation on the effect of supplementing coriander seed powder (CSP) in broilers’ diet on serum profile and immunological parameters was done. One hundred and twenty day-old commercial broiler chicks were divided into five treatment groups of 24 birds and each group having three replicates of 8 birds. T1 served as control and was offered basal diet as per BIS (2007) supplemented with antibiotics but no CSP. Treatment groups T2, T3, T4 and T5 were offered control diet plus 0.5, 1.0, 1.5 and 2.0% of CSP but no antibiotics as growth promotors. All the diets were isocaloric and iso-nitrogenous in nature. Plasma glucose and serum total cholesterol was decreased significantly (p